Alternative Solution to Sand Blanket in Vertical Drain - Zatul Iffah Bt Mohd Nor, Zatul Iffah (Universiti Teknologi Petronas, 2008)
Constrution industry in Malaysia had a brief and shortage problem in the year 1996,and as sand becoming incresingly expensive over thears,and the availability of clean sand at side can hinder the construction process,alternatives materials is needed to replace the sand application in the vertical drain system. The report explains briefly on what constitutes it soft soil; its properties and characteristic as well as problems arise from the construction on soft ground. Concept on vertical drain is illustrated to further understand hues vertical drain accelerates consolidation in soil soils, different types of vertical drains, and specifically on the prefibricated vertical drain , and the components of the vertical drains system. t